Sistem Pendukung Keputusan Penerima Bantuan Langsung Tunai Dana Desa Menggunakan Metode Smart - Huzaifa, Malisa; Refianti, Evi (MULTINETICS, 2021)
The social and economic impacts caused by the COVID-19 pandemic have had a major impact on society, especially the poor. For this reason, the government has designed various policies and programs to reduce poverty and protect the poor due to the COVID-19 pandemic, one of which is the Bantuan Langsung Tunai Dana Desa (BLT-Dana Desa) program. The BLT in Gadog Village did not escape various obstacles, such as evaluating the residents so that the delivery of direct aid funds was not right on target. Manual data entry in Gadog Village is very dangerous because there are multiple recipients and there are people who take advantage of this situation. Therefore, with the Decision Support System developed using the SMART method, it is hoped that it can determine the criteria for the community who are entitled to receive direct cash assistance from Gadog village funds. In making this system, the method used to make decisions is the Simple Multi Attribute Rating Technique (SMART) method. The SMART method is a multi-attribute decision-making method, which is a method that can have more than one attribute. This multi-attribute decision-making technique is used to support a decision maker in choosing or determining between several alternatives, and each decision maker must choose an alternative that is in accordance with the objectives that have been formulated. The Decision Support System for Bantuan Langsung Tunai Dana Desa (BLT-Dana Desa) in Gadog using the Website-Based SMART Method has been successfully built and provides information on the results of the analysis or alternatives and can rank each of these analyzes. The SMART method in this system has been able to overcome these problems based on responses from respondents (Kepala Desa, Admin and Ketua RT) of 65.69% stating that the application is appropriate and very helpful for village officials in selecting recipients of the Bantuan Langsung Tunai Dana Desa Gadog program.